A CASE REPORT OF NECROTIZING FASCIITIS OF THE NECK AND ANTERIOR CHEST WALL CAUSED BY ODONTOGENIC INFECTION IN ELDERLY: DIAGNOSIS AND MANAGEMENT IN RURAL AREA - Dorothea Kusumaningrat; Gerardo AK Laksono; Ellenora R Mustikaningrat; Oktavianus Y Ampur; Paul L Tahalele (FAKULTAS KEDOKTERAN UNIVERSITAS KATOLIK WIDYA MANDALA SURABAYA, 2023)
Introduction: Necrotizing Fasciitis (NF) is bacterial infection spreading rapidly affecting soft tissue and muscular fascia. It's life threatening and fatal, leads to tissue necrosis, sepsis, and death. It has high mortality number especially in elderly.Purpose: To report a rare case of odontogenic NF in elderly patient extending to the neck, left upper limb and anterior chest wall, diagnosed and treated in district hospital with limited facilities.Case Report: A 65 years old male with painful left neck swelling and fluctuating gangrenous appearance start form the mastoid bone to infraclavicular area crossing to the right close with sternal area. Swelling and fluctuating area also found in left axillar and left arm. Thirteen hours after hospital admission, the patient was sent to operating room to do the wound debridement. Wound care was carried out daily in intensive care unit and inpatient ward. 14 days postoperatively patient was send out to continue the wound care in outpatient department. 28 days postoperatively, skin grafting was done.Conclusion: Fourteen days postoperatively patient was sent to outpatient department to continue his wound care. After wound care in order to wound prepare for skin grafting. 28 days postoperatively, 14 days after patient discharge from hospital, skin grafting was done to close the wound defect.